Factors affecting the willingness to pay for renewable energy amongst Eastern Malaysian households: a case study - Mat Said, Aini; Goh, Mang Ling (Universiti Putra Malaysia Press, 2013)
Energy choices that are made today will greatly influence the climate of tomorrow. In addition to reducing emission of greenhouse gases, renewable energy sources will also enhance future energy security. In this vein, a study utilizing a cross-sectional research design was conducted to examine the factors affecting the willingness to pay for renewable energy (RE) among households in Malaysia. A self-administered questionnaire was used as a tool for data collection. The mean age of the respondents was 42 years, with both genders equally represented. The results indicated that that majority of the respondents were concerned about the environment and showed a positive attitude towards it. Nonetheless, there were differences in the levels of awareness and knowledge with respect to different types of RE. Age and RE awareness were found to have significant relationships with the willingness to pay for renewable energy. The results also indicated that higher educated consumers were more willing to pay for renewable energy, whereas no gender differences were observed. Strengthening support and ultimately adoption of RE products and services have to be intensified as the willingness to pay for RE by the respondents was found to be modest.